2015
DOI: 10.1038/srep17611
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Microparticles Alter Formation, Structure and Properties of Fibrin Clots

Abstract: Despite the importance of circulating microparticles in haemostasis and thrombosis, there is limited evidence for potential causative effects of naturally produced cell-derived microparticles on fibrin clot formation and its properties. We studied the significance of blood microparticles for fibrin formation, structure, and susceptibility to fibrinolysis by removing them from platelet-free plasma using filtration. Clots made in platelet-free and microparticle-depleted plasma samples from the same healthy donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 60 publications
3
74
0
1
Order By: Relevance
“…43 Further, scanning electron microscopy revealed that thrombi expose 0.1-0.5 μm in diameter, granular and CD61-positive particles, suggesting that platelet EVs adhere to fibrin. 44,45 Incorporation of EVs in thrombi in the acute phase of AMI may result in a lower concentration of platelet EVs in systemic blood.…”
Section: Discussionmentioning
confidence: 99%
“…43 Further, scanning electron microscopy revealed that thrombi expose 0.1-0.5 μm in diameter, granular and CD61-positive particles, suggesting that platelet EVs adhere to fibrin. 44,45 Incorporation of EVs in thrombi in the acute phase of AMI may result in a lower concentration of platelet EVs in systemic blood.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes were remarkably different when the effect of contraction on internal lysis was modeled by adding t‐PA prior to initiating clotting in order to recapitulate the physiological sequence of reactions . The concentration of t‐PA added (75 ng mL −1 ) did not initiate lysis until after the clot had been completely formed, as confirmed by a kinetic turbidimetry assay (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin structure and properties are greatly influenced by the presence of blood cells, namely activated platelets and erythrocytes (Aleman et al 2014; Malecki et al 2015) that form a natural and very active environment for clot formation. In addition to whole cells, the effects of circulating cell-derived microparticles on the fibrin clot structure and properties have been recently demonstrated (Zubairova et al 2015). Fibrin can interact with other components of the extracellular matrix, both filamentous and non-filamentous, that not only affects fibrin structure but imparts additional mechanical and chemical stability (Maquart and Monboisse 2014).…”
Section: Variations and Modulation Of Fibrin(ogen) Structure Andmentioning
confidence: 99%